Oviposition preference of Orius insidiosus (Hemiptera: Anthocoridae) in different herbaceous plants - Quiroz-Medina, Conrado Ronaldo (2022)
Introduction. Orius insidiosus is an omnivorous insect with an endophytic oviposition strategy, with a preference for oviposition on plants that guarantee shelter and food. Objective. To evaluate three plant species as oviposition sites for O. insidiosus on Phaseolus vulgaris (Fabaceae), Ipomoea batata (Convolvulaceae) and Portulaca oleracea (Portulacaceae). Materials and methods. The work was carried out in 2020, at the Center for Research and Reproduction of Biological Controllers of the Universidad Autónoma de Nicaragua, León, Nicaragua, León. Cutting 15-cm-long from three plants for O. insidiosus females were used as oviposition substrates: Portulaca oleracea L., Phaseolus vulgaris L., and Ipomoea batatas (L.) Lam. The experimental unit (n= 90) consisted of 15 cm long tender cuttings, individually placed in polyethylene cups using thirty replicates per treatment, using the no-choice technique. One pair of O. insidiosus was placed on each cutting. Every 24 h the cuttings were inspected to count the egg laying. Subsequently, the cuttings were removed and checked for five days to count nymphs hatching, and the final weight of the cutting was determined. Results. The highest laying values in P. oleracea cuttings with 5.90 eggs/day per cutting, followed by I. batatas with 4.10 eggs/day, and finally P. vulgaris with 2.13 eggs/day. There was evidence of variability in the posture according to the initial and final weight. The hatching values were lower than those of laying, P. oleracea had the highest hatching average with 4 individuals, followed by I. batatas with 1.5, and P. vulgaris with 0.8. Conclusions. P. oleracea showed a better preference for O. insidiosus regarding egg laying and nymph hatching. It could be validated in the field as a biological control strategy.